Layers of resistance: Understanding decision-making processes in relation to crime reporting. Issue 3 (September 2019) - Hardy, Stevie-Jade
Underreporting has been a longstanding problem for criminal justice agencies, which masks the true scale of crime taking place and prevents victims from accessing justice and support. Using empirical evidence collected from more than 2, 000 victims who came from different backgrounds and who had experienced different forms of crimes, this article proposes a new theoretical model to enhance our understanding of underreporting. This model highlights that victim decision making is influenced by structural, social, situational and individual barriers, which interact symbiotically to create layers of resistance to reporting. The article concludes by considering what steps academics, policymakers and practitioners can take to dismantle these barriers and to improve reporting rates.